Relationship amongst Noise Sensitivity, Burnout and Psychological Resilience in Community Workers - Fei Cao; Juan Li; Wei Xin; Zhibing Yang (Noise and Health)
Background: The mental health status of community workers shows the characteristics of low job satisfaction, low self-efficacy and psychological resilience, and a high sense of burnout. This research aims to explore the relationship between noise sensitivity, burnout, and psychological resilience in community workers. Methods and Material: Convenience sampling was adopted to select 169 community workers from five communities as research objects for an anonymous questionnaire survey. A general questionnaire was used to collect the general information of the respondents. Noise sensitivity, burnout and psychological resilience scales were adopted to analyse the correlation amongst noise sensitivity, burnout and psychological resilience in community workers. Univariate and multivariate logistics regression analyses were used to analyse the influencing factors of job burnout and psychological resilience in community workers. Results: A total of 169 questionnaires were distributed, and after excluding 6 unqualified questionnaires, 163 valid questionnaires (96.45%) were collected. The scores on the noise sensitivity, burnout and psychological resilience scales were 63.80 ± 9.69, 78.57 ± 10.12 and 54.18 ± 8.77 points, respectively. The results of the correlation analysis showed that in community workers, the noise sensitivity score was negatively correlated with the psychological resilience score (P < 0.001) and positively correlated with the burnout score (P < 0.001). The burnout and psychological resilience scores of community workers showed statistical differences with different ages, working years and disposable monthly family income (P < 0.001). Multiple linear regression results revealed that noise sensitivity, age, working years and disposable monthly family income had an effect on burnout and psychological resilience scores (P < 0.001). Conclusion: In community workers, noise sensitivity is positively correlated with burnout and negatively correlated with psychological resilience. This study provides a certain research basis for conducting relevant psychological research and interventions.